How age of first exposure to familial gambling, and gambling frequency affect problematic gambling behaviours. - Yee, Jasmine Hui Wen. (2013)
This paper aims to investigate how problematic gambling behaviour is affected by the age of first exposure to familial gambling and how frequent one engages in gambling activities. It also compares the predictive value of exposure age and gambling frequency for problematic gambling behaviours. Gambling frequency was hypothesized to better predict the prevalence of problematic gambling behaviours as compared to age of first exposure to familial gambling (hypothesis 1). Based on results of hypothesis 1, it was further hypothesized that either risk-taking propensity (hypothesis 2a) or gambling attitudes (hypothesis 2b) would mediate the relationship between gambling frequency and problematic gambling behaviours. A questionnaire study (SOGS, GBQ and GSEQ) was conducted followed by a simulated gambling game (Blackjack). Results demonstrated a significant positive relationship between gambling frequency and problematic gambling behaviours while an insignificant relationship was found between age of first exposure and problematic gambling. Thus, gambling frequency appears to be a better predictor of problem gambling than that of age of exposure. Next, mediation by either risk-taking propensity or gambling attitudes were not supported, but gambling attitudes consistently predicted problematic gambling behaviours. This paper provides new insights to the comparisons between different risk factors to problem gambling and demonstrates the importance of gambling attitudes to problem gambling.